Coating technology of self-cleaning glass coating

Through water-based nano-composite coatings and gradient curing UV cross-linking technology, the hydrophilicity and durability problems of self-cleaning glass coatings have been solved, and a self-cleaning glass coating with low-temperature film formation, high transmittance and high adhesion has been achieved, which is suitable for the fields of construction, automobiles and photovoltaics.

CN120590071APending Publication Date: 2025-09-05XINXIANG INST OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510792601.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

Existing self-cleaning glass coating technology has difficulty in balancing hydrophilicity and durability. The high-temperature curing process limits the application of flexible substrates. The low-temperature curing coating has weak adhesion and low transmittance. Existing technologies have failed to effectively solve the problems of interface compatibility and gradient curing control.

Method used

A water-based nanocomposite coating is applied to the surface of the glass substrate by roller coating or spraying, combined with gradient temperature curing and ultraviolet irradiation to form a self-cleaning glass coating with a TiO2/SiO2 core-shell structure. A polyurethane-modified silane coupling agent is used to enhance adhesion, and gradient curing and ultraviolet cross-linking are used to achieve low-temperature film formation.

Benefits of technology

A self-cleaning glass coating with high adhesion and high transmittance at low temperatures has been achieved. The coating exhibits excellent anti-icing and anti-fouling properties in extreme environments and is suitable for construction, automobiles, and photovoltaics.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a coating technology of a self-cleaning glass coating, which adopts a water-based paint containing nano TiO2 / SiO2 hybrid sol (core-shell structure), a polyurethane modified silane coupling agent and a flatting agent, and forms a 150-300nm super-hydrophilic coating (the contact angle is less than or equal to 5 degrees) on the surface of glass through a synergistic process of gradient curing (three-stage heating at 80-150 DEG C) and ultraviolet radiation (a main wave band of 365nm and an auxiliary wave band of 280-320nm). The technology breaks through the bottleneck that low-temperature curing and high adhesive force are difficult to be compatible, and the contact angle of the coating is still lt after damp-heat aging; 10 degrees, the light transmittance loss lt; and 3%, the photovoltaic module is suitable for building curtain walls, automobile windshields and photovoltaic modules. The method comprises the following steps: (1) bonding a polyurethane chain segment with a mechanical interlocking enhanced interface through a hydrogen bond; (2) the SiO2 shell layer improves the TiO2 quantum efficiency; and (3) equipment zoned humidity control and inert atmosphere oxidation inhibition are realized, and unification of self-cleaning performance, optical performance and mechanical durability is realized by an environment-friendly process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional glass surface treatment, in particular to a coating technology for a self-cleaning glass coating. Background Art

[0002] Current self-cleaning glass coating technology faces a dilemma: it's difficult to balance hydrophilicity and durability. Super-hydrophilic coatings (contact angles <5°) can remove contaminants through a water film, but their high surface energy makes them susceptible to adsorbing particulate contaminants, and the hydrophilic groups are prone to decomposition under long-term UV irradiation. Hydrophobic coatings rely on rolling low-surface-energy materials to remove dust, but their microstructure reduces light transmittance and exhibits poor mechanical stability. Furthermore, high-temperature curing processes (>300°C) restrict their application to flexible substrates, while low-temperature curing coatings suffer from weak adhesion and insufficient crosslinking, making it difficult to meet the comprehensive environmental adaptability and lifespan requirements of applications in the construction, automotive, and photovoltaic sectors.

[0003] Existing technologies attempt to improve performance through photocatalytic materials (such as TiO2) or organic-inorganic hybrids, but they fail to address the issues of interfacial compatibility and gradient curing control: the resin matrix and nanofillers easily separate, and stress concentration during the curing process causes microcracks, ultimately leading to coating peeling or hydrophilicity degradation. A coating technology that combines low-temperature film formation, high light transmittance, and long-lasting self-cleaning properties is urgently needed. Summary of the Invention

[0004] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of this application to avoid obscuring the purpose of this section, the abstract and the title of the invention, and such simplifications or omissions should not be used to limit the scope of the present invention.

[0005] In view of the above problems in the prior art, the inventors proposed the present invention.

[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a coating technology for a self-cleaning glass coating.

[0007] To solve the above technical problems, the present invention provides the following technical solution: a coating technology for a self-cleaning glass coating, comprising the following steps:

[0008] (a) applying the water-based nanocomposite coating to the surface of the pretreated glass substrate by roller coating, spraying or dipping, with the wet film thickness controlled to be 150-300 μm;

[0009] (b) pre-curing at 80-100° C. for 3-8 minutes in an environment with a humidity of 40-60% to form a primary cross-linked network;

[0010] (c) curing by a three-stage gradient temperature ramp: 80°C → 100°C (heating rate 5°C / min, hold for 5 min), 100°C → 120°C (heating rate 5°C / min, hold for 5 min), and constant temperature at 120°C for 10-15 minutes to complete the silane dehydration condensation reaction;

[0011] (d) UV irradiation for 10-30 seconds (wavelength 365 nm, intensity 80-100 mW / cm 2 ), initiating free radical cross-linking curing.

[0012] As a preferred solution of the coating technology of the self-cleaning glass coating described in the present invention, the water-based nano-composite coating comprises, by weight, 20-30 parts of nano-TiO2 / SiO2 hybrid sol (TiO2:SiO2 molar ratio of 1:0.3-0.5, particle size of 20-50nm), 10-15 parts of water-based polyurethane modified silane coupling agent (prepared by reacting γ-aminopropyltriethoxysilane and polyurethane prepolymer in a ratio of 1:2-3), 0.5-1 part of sodium carboxymethyl cellulose leveling agent, and deionized water to make up to 100 parts.

[0013] As a preferred solution of the coating technology of the self-cleaning glass coating of the present invention, the nano-TiO2 / SiO2 hybrid sol is prepared by a sol-gel method, wherein SiO2 is coated on the surface of TiO2 to form a core-shell structure with a shell thickness of 5-10nm.

[0014] As a preferred solution of the coating technology of the self-cleaning glass coating of the present invention, wherein: in the pre-curing stage of step (b), far infrared heating is adopted, and the temperature deviation of the substrate surface is ≤±2°C.

[0015] As a preferred solution of the coating technology of the self-cleaning glass coating of the present invention, in the step (c), an inert gas is introduced during the gradient curing process, and the oxygen concentration is controlled below 200 ppm.

[0016] As a preferred solution of the coating technology of the self-cleaning glass coating of the present invention, wherein: after the ultraviolet irradiation in step (d), deep ultraviolet light with a wavelength of 280-320 nm is used for auxiliary treatment for 5-10 seconds to improve the density of the coating.

[0017] A self-cleaning glass prepared by a coating technology of a self-cleaning glass coating is characterized by: a surface having a micro-nano composite structure, a water contact angle ≤ 5°, a photocatalytic degradation efficiency of methylene blue ≥ 95% / 4h, a coating thickness of 150-300nm, and a transmittance loss of <3%.

[0018] As a preferred solution of the self-cleaning glass of the present invention, the contact angle of the coating is ≤15° at -20°C, and the adhesion retention rate is ≥90% after 1000 wiper friction tests.

[0019] A coating device includes a spray module, a temperature-controlled curing box and an ultraviolet irradiation unit, wherein: the curing box is divided into a pre-curing zone (80-100°C, controllable humidity) and a gradient temperature rising zone (120-150°C, inert gas atmosphere), and the ultraviolet irradiation unit contains a main light source with a wavelength of 365nm and an auxiliary light source with a wavelength of 280-320nm.

[0020] As a preferred solution of the coating equipment of the present invention, the spraying module is integrated with an electrostatic atomization device, the atomization particle size is 10-50 μm, and the electric field strength is 30-50 kV.

[0021] Beneficial effects of the invention: This technology overcomes performance bottlenecks through the synergistic combination of component compounding and process: In the water-based nanocomposite coating, a polyurethane-modified silane coupling agent provides flexible chain segments to buffer stress, sodium carboxymethyl cellulose regulates leveling to avoid orange peel, and the TiO2 / SiO2 core-shell structure inhibits photogenerated carrier recombination, making the coating both super-hydrophilic (contact angle ≤ 5°) and highly photocatalytic (degrading 95% of pollutants in 4 hours). The gradient curing process matches the material reaction kinetics, with pre-curing forming an initial cross-linked network, step-by-step temperature increases to promote complete condensation reactions, and ultraviolet radiation to enhance three-dimensional cross-linking, achieving low-temperature film formation at 120°C with adhesion levels of up to level 5.

[0022] The coating performs exceptionally well in extreme environments: anti-icing at -20°C (contact angle ≤ 15°), transmittance retention >97% after 1000 hours of wet heat aging, and no peeling after a wiper friction test. The equipment integrates inert atmosphere protection and dual-band UV curing to prevent oxidative side reactions and improve coating density. The overall solution covers three major application scenarios: construction, automotive, and photovoltaics, achieving green manufacturing with a VOC content of <50g / L. DETAILED DESCRIPTION

[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0025] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it constitute a separate or selective embodiment that is mutually exclusive with other embodiments.

[0026] Example 1

[0027] This embodiment provides a coating technology for a self-cleaning glass coating, specifically, a coating implementation for building curtain wall glass.

[0028] Recipe composition:

[0029] Nano-TiO2 / SiO2 hybrid sol: 25 parts (TiO2:SiO2 molar ratio 1:0.4, SiO2 shell thickness 8nm, particle size 30±5nm);

[0030] Waterborne polyurethane modified silane coupling agent: 12 parts (prepared by reacting γ-aminopropyltriethoxysilane with polyether polyurethane prepolymer at a ratio of 1:2.5);

[0031] Sodium carboxymethyl cellulose (CMC): 0.7 parts (viscosity 1200 mPa·s);

[0032] Deionized water: 62.3 parts.

[0033] Preferably, the hybrid sol is prepared by a non-hydrolytic sol-gel method, and SiO2 is coated on the surface of anatase TiO2 to form a core-shell structure.

[0034] Coating process:

[0035] Substrate pretreatment: 6 mm float glass was ultrasonically cleaned with ethanol for 10 min and dried with nitrogen;

[0036] Roller coating: Use micro gravure roller coater, line speed 2m / min, wet film thickness 200μm;

[0037] Gradient curing:

[0038] Pre-curing: 85℃ / 5min (humidity 50%, far-infrared heating, surface temperature difference ≤±2℃);

[0039] Main curing: three-stage heating: 80℃→100℃ (rate 5℃ / min, keep warm for 5min), 100℃→120℃ (rate 5℃ / min, keep warm for 5min), constant temperature at 120℃ for 15min.

[0040] UV enhancement: 365nm main light source (100mW / cm 2 Irradiation 20s) + 300nm auxiliary light source (50mW / cm 2 irradiation for 5 s).

[0041] Performance Verification:

[0042] Test items The present invention <![CDATA[Comparative Example (without SiO2 shell)]]> Initial contact angle 4.2° 12.5° Contact angle after 1000h wet heat aging 8.7° >35° Adhesion (ISO 2409) Level 5 Level 3 Transmittance (550nm) 91.5% 88.3%

[0043] Mechanism of Action: -NH- in the polyurethane chain forms a hydrogen bond network with -SiOH on the glass surface (FTIR characteristic peak at 1620 cm-1). Upon UV irradiation, this hydrogen bond transforms into Si-O-Si covalent bonds (XPS shows a Si2p binding energy shift of +1.2 eV). The SiO2 shell inhibits the recombination of photogenerated holes, increasing the quantum efficiency to 68% (compared with the PL spectral quenching rate).

[0044] This embodiment uses triple collaboration:

[0045] Chemical bonding between the nanosol and the coupling agent: In the TiO2 / SiO2 core-shell particles, the silanol (Si-OH) groups in the SiO2 shell undergo dehydration condensation with the amino groups (-NH2) of the polyurethane-modified silane, forming Si-N covalent bonds (XPS detected a Si2p binding energy shift of 102.5 eV). Simultaneously, long polyurethane chains interspersed the interstitial spaces between the hybrid particles (TEM showed spacing ≤2 nm), enhancing interfacial bonding through hydrogen bonding and van der Waals forces, resulting in a coating hardness of 4H (ISO 15184).

[0046] Gradient curing and UV energy timing match: the pre-curing stage (85°C) promotes the hydrolysis of silane to form silanol groups, and the gradient temperature is increased to 120°C to drive the condensation reaction (DSC shows that the exothermic peak width decreases by 40%). UV irradiation excites TiO2 to produce hydroxyl radicals (·OH), which attack the carbon-nitrogen bonds in the polyurethane to form aldehyde groups (FTIR 1720cm - 1 characteristic peak), and the aldehyde groups further condensed with Si-OH to form a dense network (cross-linking density increased by 32%).

[0047] Charge regulation effect of leveling agent: carboxyl anions of CMC are adsorbed on the surface of TiO2 / SiO2 particles (Zeta potential increases from -25mV to -8mV), reducing the viscosity of the system and accelerating leveling (leveling time is shortened to 40 seconds). Laser confocal microscopy shows that the surface roughness Ra = 35nm.

[0048] Example 2

[0049] This embodiment provides a coating technology for a self-cleaning glass coating, which is implemented on automobile windshields.

[0050] Recipe improvements:

[0051] Increase the polyurethane modified silane coupling agent to 14 parts (to improve flexibility);

[0052] Add 0.3 parts of perfluorohexylethyl acrylate (surface energy reduced to 18 mN / m);

[0053] The molar ratio of SiO2 in the hybrid sol is adjusted to 1:0.45 (to enhance the low-temperature hydration ability).

[0054] Process innovation:

[0055] Substrate treatment: curved tempered glass (curvature radius R800mm) plasma activation for 2 minutes;

[0056] Electrostatic spraying: voltage 50kV, atomization pressure 0.3MPa, droplet size 20±5μm;

[0057] Inert atmosphere curing:

[0058] Pre-curing: 90℃ / 3min

[0059] Deep UV assistance: 300nm wavelength irradiation for 10s (penetration depth increased by 40%).

[0060] Furthermore, dynamic pressure control (0.5-1.0 MPa alternating) was used in the gradient solidification stage to suppress surface sagging.

[0061] Extreme environment testing:

[0062] Test conditions Performance Results Industry Standards -20℃ contact angle 14.8° ≤20° Wiper friction 1000 times The contact angle increased to 9.5° without shedding ≤15% increase Salt spray test 240h Adhesion retention rate 92% ≥85%

[0063] Innovative analysis: Perfluorinated chains are oriented on the coating surface (TOF-SIMS detection of F - The -CF3 group reduces the freezing point interfacial tension and can be used to decompose residual tertiary amines (HPLC detection of residual amines <0.1ppm), thus reducing the permeation channels of water and oxygen.

[0064] This scheme uses the dynamic balance between fluorocarbon chains and hydrophilic groups: the -CF3 group of perfluorohexylethyl acrylate (surface energy 6.7mJ / m 2 ) are oriented on the coating surface (TOF-SIMS depth profiling shows an F / C ratio >1.5), while a high SiO2 content (molar ratio 1:0.45) provides hydroxyl groups to capture water molecules. At -20°C, a "fluorocarbon domain blocks ice / hydrophilic domain melts ice" microstructure is formed (cryo-electron microscopy reveals ice crystal size ≤3μm), with an ice adhesion strength of <100kPa (compared to the industry standard of <150kPa).

[0065] Collaborative purification of deep ultraviolet and inert atmosphere: 300nm deep ultraviolet light has a penetration depth of 180nm (compared to 365nm only 80nm), which can crack the residual tertiary amine groups to generate methyl radicals (GC-MS detects methane release). Nitrogen atmosphere inhibits the oxidation of titanium atoms (XRD shows no Ti 3+ defect peak), so that the carbonyl index is only 0.08 after 2000h of QUV aging (0.35 for the untreated group).

[0066] Surface adaptation through electrostatic adsorption and rheological control: 50kV high-voltage electric field makes the droplet charge-to-mass ratio >2mC / kg (Malvern measurement), enhancing surface adhesion; 0.5-1.0MPa dynamic pressure triggers shear thinning (viscosity drops by 40% instantaneously), making the coating thickness deviation on the R800mm curved surface <10%.

[0067] Example 3

[0068] This embodiment provides a coating technology for a self-cleaning glass coating, specifically, a coating implementation for photovoltaic module glass.

[0069] Functional modification:

[0070] Add 5 parts of ITO nanowires (diameter 20 nm, aspect ratio 50:1), with a square resistance of 95Ω;

[0071] The SiO2 molar ratio in the hybrid sol is increased to 1:0.5 (hydroxyl density 8.2 / nm 2 );

[0072] Curing process: 120℃ constant temperature for 20min (cancel the gradient heating to adapt to the float glass production line).

[0073] Specific implementation steps:

[0074] Dipping and pulling: speed 100 mm / min, dipping time 30 s;

[0075] High humidity pre-curing: 95°C / 3min (humidity 60%, promoting hydration of hydroxypropyl chitosan);

[0076] UV enhancement: 365nm single-band irradiation for 30s (to avoid photothermal attenuation of ITO).

[0077] As a preferred solution, ITO nanowires are pre-dispersed in P123 micelles to prevent agglomeration (TEM shows line spacing ≥ 50nm)

[0078] Comparison of photoelectric performance:

[0079] parameter The present invention Conventional self-cleaning coating Improvement rate Average light transmittance (400-1100nm) 92.8% 90.1% +3.0% Haze 1.2% 2.8% -57% Dust loss rate (year) 0.28% 0.75% -63%

[0080] Synergistic principle: ITO nanowires build a conductive network (square resistance 95Ω), which inhibits dust adsorption through electrostatic repulsion (Zeta potential -35mV). High SiO2 content enables a surface hydroxyl density of 8.2 / nm. 2 (XPS O1s fitting analysis), morning dew forms a continuous water film, reducing light scattering.

[0081] Synergy of this example:

[0082] Optical synergy of ITO nanowires and hybrid sols: A gradient refractive index layer (n = 1.9 → 2.1, measured by ellipsometry) constructed from ITO (refractive index 1.9) and TiO2 / SiO2 (refractive index 2.1) reduced the interface reflectivity from 8.2% to 3.5%. The ITO nanowire network (interline spacing 50±5nm) induced surface plasmon resonance (UV-Vis absorbance at 550nm +0.15), improving the utilization of photogenerated electrons (device output power +2.1%).

[0083] Dust-proof synergy of hydroxyl enrichment and electrostatic repulsion: High SiO2 content (molar ratio 1:0.5) makes the surface hydroxyl density reach 8.2 / nm 2 Morning dew forms a super-hydrophilic film. The ITO network with a square resistance of 95Ω charges dust to -15mV (Zeta potential), reducing dust accumulation by 63% due to electrostatic repulsion.

[0084] Defect repair with constant temperature curing and UV: 120°C constant temperature for 20 minutes to match the production line speed (15m / min), UV irradiation activates oxygen vacancies in ITO (PL spectrum quenching rate 82%), avoiding resistance increase (compared to the gradient curing group, the square resistance is +50%)

[0085] The three examples together demonstrate the core innovations and beneficial effects of this technology:

[0086] It combines low-temperature film-forming properties with high adhesion. The flexible chain segments of the polyurethane-modified silane coupling agent buffer thermal stress (Tg=-45°C). Combined with gradient curing (80-120°C) and dual-band UV irradiation (365nm+300nm), it achieves complete cross-linking at 120°C, with adhesion reaching level 5, thus solving the problem of substrate deformation caused by high-temperature curing.

[0087] Breakthrough in self-cleaning durability: The SiO2 shell layer (thickness 5-10nm) in the TiO2 / SiO2 core-shell structure inhibits photocorrosion, so that the contact angle remains <10° after 1000h of wet-heat aging; the directional arrangement of fluorocarbon surfactants makes the low-temperature contact angle of -20℃ ≤15°, breaking through the bottleneck of low-temperature failure of hydrophilic coatings.

[0088] Multifunctional integrated adaptability: Architectural glass uses roller coating + inert atmosphere curing to ensure film uniformity; automotive curved glass suppresses sagging through electrostatic atomization (droplets 20μm) and dynamic pressure control; photovoltaic glass introduces ITO nanowires (square resistance <100Ω) to reduce dust accumulation loss rate by 63%, while taking into account light transmittance (>92.8%) and dust protection functions.

[0089] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A coating technology for a self-cleaning glass coating, characterized by: The following steps are involved: (a) applying the water-based nanocomposite coating to the surface of the pretreated glass substrate by roller coating, spraying or dipping, with the wet film thickness controlled to be 150-300 μm; (b) pre-curing at 80-100° C. for 3-8 minutes in an environment with a humidity of 40-60% to form a primary cross-linked network; (c) curing by three-stage gradient temperature rise: 80°C → 100°C, 100°C → 120°C, and constant temperature at 120°C for 10-15 minutes to complete the silane dehydration condensation reaction; (d) UV irradiation for 10-30 seconds to initiate free radical crosslinking and curing.

2. The coating technology of the self-cleaning glass coating according to claim 1, characterized in that: The water-based nano composite coating comprises, by weight, 20-30 parts of nano TiO2 / SiO2 hybrid sol, 10-15 parts of water-based polyurethane modified silane coupling agent, 0.5-1 part of sodium carboxymethyl cellulose leveling agent, and deionized water to make up to 100 parts.

3. The coating technology of the self-cleaning glass coating according to claim 2, characterized in that: The nano-TiO2 / SiO2 hybrid sol is prepared by a sol-gel method, wherein SiO2 is coated on the surface of TiO2 to form a core-shell structure with a shell thickness of 5-10 nm.

4. The coating technology of the self-cleaning glass coating according to claim 1, characterized in that: In the pre-curing stage of step (b), far infrared heating is used, and the surface temperature deviation of the substrate is ≤±2°C.

5. The coating technology of the self-cleaning glass coating according to claim 1, characterized in that: In the step (c) gradient curing process, an inert gas is introduced and the oxygen concentration is controlled below 200 ppm.

6. The coating technology of the self-cleaning glass coating according to claim 1, characterized in that: After the ultraviolet irradiation in step (d), deep ultraviolet light with a wavelength of 280-320 nm is used for auxiliary treatment for 5-10 seconds to improve the density of the coating.

7. A self-cleaning glass prepared by the coating technology of the self-cleaning glass coating according to any one of claims 1 to 6, characterized in that: The surface has a micro-nano composite structure, the water contact angle is ≤5 degrees, the photocatalytic degradation efficiency of methylene blue is ≥95% / 4h, the coating thickness is 150-300nm, and the transmittance loss is <3% (wavelength 550nm).

8. The self-cleaning glass according to claim 7, wherein: The contact angle of the coating is ≤15° under a -20°C environment, and the adhesion retention rate is ≥90% after 1000 wiper friction tests.

9. A coating device comprising a spraying module, a temperature-controlled curing box, and an ultraviolet irradiation unit, characterized in that: The curing box is divided into a pre-curing zone and a gradient temperature rising zone, and the ultraviolet irradiation unit includes a main light source with a wavelength of 365nm and an auxiliary light source with a wavelength of 280-320nm.

10. The coating device according to claim 9, characterized in that: The spraying module is integrated with an electrostatic atomization device, with an atomization particle size of 10-50 μm and an electric field strength of 30-50 kV.

Citation Information

Cited By

  • High-resilience eTPU foaming material and preparation process thereof

    CN121758810A